Relationship between fat distribution ratio and blood pressure in obese adolescents - Henny Marina; Dany Hilmanto; Julistio Tb Djais (Indonesian Pediatric Society Publishing House, 2016)
Background The incidence of obesity in big cities increases significantly. The association between obesity and increased risk of cardiovascular disease and hypertension in adults has been known but less information is available in adolescents. Similarly, the relationship between body-fat distribution and cardiovascular diseases in adolescents is less clear tha that in adults. Objective This study aimed to determine the association between body fat distribution and increased blood pressure in obese adolescents in Bandung. Methods This cross-sectional study was conducted from June to August 2006. Subjects were students aged 15-18 years at high schools in Bandung with body mass index (BMI) measured using CDC chart 2000 (> P95) and increased blood pressure (> P90) depended on age and gender according to National High Blood Pressure Education Program Working Group on High Blood Pressure in Children and Adolescents 2004. Waist-to-hip ratio (central fat), and subscapula skinfold-to-triceps skinfold ratio (peripheral fat) were used to measure fat distribution. Correlation between body fat distribution and blood pressure was analyzed using Pearson correlation statistical test. Results Out of 3170 adolescents examined, 34 obese adolescent girls and 43 obese adolescent boys had increased blood pressure. Correlation between waist-to-hip ratio and systole blood pressure in boys showed by r=0.495; P=0.003 and girls showed r=0.494; P=O.OOl. Correlation between subscapula skinfold-to-triceps skinfold ratio in boys showed r=0.289; P=0.097 and girls showed by r=0.248; P=0.109. Conclusion Central fat is moderately correlated with increased blood pressure in obese adolescents.